Friction and wear behaviour of an Al-based metal-matrix composite against automobile friction materials. (1st January 2002) - Straffelini, G.; Pellizzari, M.; Maines, L.; Molinari, A.
An Al-based metal matrix composite containing 20 vol.% of SiC particles was submitted to dry sliding tests to verify its suitability for the production of brake discs for the automobile industry. Three types of friction materials were investigated, and tests against cast iron were also carried out for comparison. The tests were carried out at increasing applied loads, and the evolution of friction coefficient, surface temperature and wear was monitored. The obtained results are only partially promising. Friction is low and decreases as the applied load and surface temperature are increased. The high thermal conductivity of the material does not play the expected role. Wear, finally, was negligible, but surface damage was present and intense, and this could produce severe wear in the case of prolonged sliding.